Ingenious the unintended consequences of human innovation - Gluckman, Peter D. 1949-; Hanson, Mark A. 1949- (Harvard University Press, 2019)
Evolution is the process by which species adapt over time to their environments. The tricky part about human evolution is that, as technology builders, we have the power to alter our environments--and even build new, unprecedented conditions in which to immerse ourselves. This is an extraordinary mastery of nature. Not only can we keep the ruthless process of natural selection at bay; we can force nature to bend to us. But the effects of upending the evolutionary process are not as simple as they may seem. Gluckman and Hanson, both leaders in the exciting new field of evolutionary medicine, explore how, even as our ingenious innovations allow us to thrive, they create unforeseen consequences that demand further ingenuity. We've made the environments around us more food-rich, for example--but at the cost of rampant obesity. We've learned to wipe out the pathogens that most commonly make us ill, but in doing so encouraged the rise of antibiotic-resistant superbugs that our bodies are desperately unable to fend off. We have created new information and communication environs that stimulate our intellectual curiosity and challenge our abstract thinking capacities. The downsides are new forms of social dysfunction and sources of psychological stress. Ironically, in many ways, our efforts to be more comfortable have led to dire consequences for our health. Every time we transform our world, we are confronted by a world that challenges us anew. Ingenious opens our eyes to the dangers we face and offers solutions we cannot ignore.--
Keywords: Innovation; Technischer Fortschritt; Mensch; Nachhaltigkeit; Fortschrittsgedanke; Human evolution; Technological innovations / Health aspects; Civilization, Modern / Health aspects